KAJIAN KAWASAN: PENDEKATAN STRATEGIS DALAM PENELITIAN ARKEOLOGI DI INDONESIA DEWASA INI - Mundardjito (BRIN, 1995)
If I or you as an individual will enter a meeting room, at the entrance you may think for a moment as you look left and right, which chair will you be sitting on. If you were a participant, and not an important official, you probably wouldn't choose a place in the front row of seats. You might choose to sit in a row of chairs a little back because there are already a number of your friends sitting there so you feel 'warm' and occasionally can steal the opportunity to greet a close friend who has not met for a long time. Or, long before entering the meeting room, you have decided in advance that you will sit in the second row so that you can focus more on hearing the presenters' descriptions without the interference of peers who they know will definitely invite them to chat outside of the subject matter in the session. Decision making to place ourselves in that space unit is influenced or determined by thoughts and feelings to socialize with friends or vice versa.